Trait agreeableness moderates the relationship between induced state agreeableness and feeling states - Leikas, Sointu (Frontiers in Psychology, 2026)
The idea that counterdispositional behavior is depleting, stressful, or less rewarding than trait-consistent behavior has received much attention in personality science in recent years. In an experience sampling study with a within-person intervention design (N = 74), participants first went through a baseline ESM protocol and were then prompted to behave in an agreeable and conscientious way for 4 days each. Trait Agreeableness moderated the relationship between agreeable behavior and momentary feelings; the higher the participant's trait Agreeableness, the better and less stressed they felt after behaving agreeably. In contrast, trait Conscientiousness did not moderate conscientious behavior-outcome relations. The results were in line with previous studies on counterdispositional Conscientiousness and suggested that those with higher trait Agreeableness may find it easier or more rewarding to act agreeably than those with lower trait Agreeableness.